Comprehensive screening of Mg corrosion inhibitors. (November 2017) - Lamaka, S.V.; Vaghefinazari, B.; Mei, Di; Petrauskas, R.P.; Höche, D.; Zheludkevich, M.L.
Highlights: 151 chemical compounds are tested towards their inhibiting effect on Mg alloys. New inhibitors are tested on AZ31, AZ91, AM50, WE43, ZE41, Elektron 21 and three grades of pure magnesium. The extensive database of magnesium corrosion inhibitors is set up. A number of new inhibitors are discovered with efficiency exceeding that of chromate. The salts of pyridinedicarboxylic and salicylic acids are the most efficient and universal Mg corrosion inhibitors. Abstract: This work presents the results of a systematic screening for magnesium corrosion inhibitors. The ability to form stable soluble complexes with Fe ii/iii was considered on first place when choosing the compounds for hydrogen evolution tests. Inhibiting effect of 151 individual compounds was tested towards six alloys (AZ31, AZ91, AM50, WE43, ZE41 and Elektron 21) and three grades of pure magnesium. Newly identified and previously reported inhibitors are ranked by their inhibiting efficiency and compared with Cr (VI) reference. A number of new inhibitors are discovered with efficiency exceeding that of chromate.